Synthesis and Characterization of PMMA/Nanoclay Composite as an Excellent Dental Material - Md. Alamgir (2024)
The present study reports the synthesis of poly (methyl methacrylate) (PMMA)/nanoclay-based nanocomposites via melt compounding using a twin extruder process. PMMA was chosen as a matrix material and various weight fractions of nanoclay (NC) nanoparticles (1 wt.% and 2 wt.%) were used as reinforcement. The processed nanocomposites were comprehensively characterized through simple indentation analysis, scratch analysis, and field emission scanning electron microscopy (FESEM) analysis. The variation in the mechanical properties with the addition of various wt. % of nanoclay in the composites was examined. The estimation of the mechanical aspects of the nanocomposites showed that the utilization of Nanoclay as a reinforcing factor increased specific strength of polymer. The morphological analysis depicted the formation of composites with uniform dispersion of nanoclay within the polymer matrix. The successful compatibilization in Nanoclay and the polymer pattern developed the engineering attributes. Finally, this event may combine the design aimed at the formation of a different compatibilized Nanoclay founded blend concerning dental treatments.